Genetic alterations driving metastatic colony formation are acquired outside of the primary tumour in melanoma - Melanie Werner-Klein (Nature Portfolio, 2018)
For several cancer types, mouse models indicate that metastasis occurs early. Here, the authors show that human melanoma cells disseminate early and illustrate a genetic colonisation signature that evolves in parallel at different sites.